2007
DOI: 10.1242/jeb.002857
|View full text |Cite
|
Sign up to set email alerts
|

Physiological regulation of glucose transporter (GLUT4) protein content in brown trout (Salmo trutta) skeletal muscle

Abstract: SUMMARY In brown trout, red and white skeletal muscle express the insulin-regulatable glucose transporter 4 (btGLUT4). We have previously shown that the mRNA expression of btGLUT4 in red muscle, but not white muscle, is altered under experimental conditions designed to cause changes in the plasma levels of insulin, such as fasting, insulin and arginine administration. In order to determine whether changes of btGLUT4 expression at the mRNA level are correlated with changes at the protein level, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 33 publications
2
24
1
Order By: Relevance
“…The observed ability of insulin to stimulate GLUT4 mRNA expression in vitro in trout muscle cells is consistent with the results of a previous in vivo study from our group that established a relationship between insulin plasma levels and GLUT4 mRNA levels in skeletal muscle in trout (8). More recently, we have shown that insulin and arginine administration increase, whereas fasting decreases GLUT4 protein content in trout skeletal muscle (12), supporting the notion that circulating insulin may regulate the expression of GLUT4, both at the mRNA and protein levels, in skeletal muscle. Therefore, the present study provides the first evidence in fish (and in nonmammalian vertebrates) that insulin is able to regulate GLUT4 mRNA content in trout skeletal muscle by exerting its function directly on muscle cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The observed ability of insulin to stimulate GLUT4 mRNA expression in vitro in trout muscle cells is consistent with the results of a previous in vivo study from our group that established a relationship between insulin plasma levels and GLUT4 mRNA levels in skeletal muscle in trout (8). More recently, we have shown that insulin and arginine administration increase, whereas fasting decreases GLUT4 protein content in trout skeletal muscle (12), supporting the notion that circulating insulin may regulate the expression of GLUT4, both at the mRNA and protein levels, in skeletal muscle. Therefore, the present study provides the first evidence in fish (and in nonmammalian vertebrates) that insulin is able to regulate GLUT4 mRNA content in trout skeletal muscle by exerting its function directly on muscle cells.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, little is known about the regulation of the expression of fish GLUT4 by insulin or IGF-I. Previous in vivo studies from our laboratory have shown a direct correlation between blood insulin levels and mRNA and protein expression levels of GLUT4 in trout red skeletal muscle (8,12). In contrast to GLUT4, GLUT1 mRNA expression in both white and red trout skeletal muscle remained invariable to the changes in plasma insulin (8).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Glucose uptake mediated by the facilitative insulin-regulated glucose transporter GLUT4 homologue in white muscle and fat tissues and by GLUT2 in the liver has been reported in trout (Capilla et al, 2002;Diaz et al, 2007a;Diaz et al, 2007b;Krasnov et al, 2001). Fish glucose transporters GLUT2 and GLUT4 are characterized by a lower affinity for glucose, which may at least partly explain the persistent post-prandial hyperglycemia observed in trout fed with carbohydrates (Capilla et al, 2004a;Krasnov et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…In rainbow trout, a system similar to that proposed in mammals involved in the detection of changes in circulating glucose levels by pancreatic ␤-cells and glucose-excited neurons in the hypothalamus and the brain stem appears to be functional and inducible (48,49). Glucose uptake mediated by the facilitative insulin-regulated glucose transporter GLUT4 homolog in white muscle and fat tissues and by GLUT2 in liver are observed in trout (6,9,10,30). At the metabolic level, most key enzymes involved in carbohydrate metabolism are described in fish (7).…”
mentioning
confidence: 93%